Notions of Young Women without Children about Childbirth - Kisdi, Barbara (European Journal of Mental Health, 2018)
Aim: The aim of the study was to find out what kind of imaginations and expectations of Hungarian young, childless women have about childbirth. In addition to mapping intentions and expectations, our questions focused on how they think about the circumstances, ways and types of childbirth and we asked them what they know about opportunities and procedures based on their previous experiences. Methods: In our university research we conducted a qualitative examination using the method of depth interviewing young women about their birth plans (n. 154, 18-35 years old). The selection of interviewees was randomly recruited from the circle of acquaintances of university students. The data collection took place during 2016. The study used content analysis. Results: In the case of randomly questioned women, the issue of the quality of birth is usually not part of either their primary or secondary socialisation. The source of imagination on childbirth is usually the media and negative family stories which describe birth as a dangerous and painful event and which mainly transform young women-s attitudes to pregnancy and childbirth. Accordingly, the majority of interviewees do not consider themselves competent in their own childbirths, and intend to rely essentially on external authority. Conclusions: On the basis of the examination it appears that the information obtained through formal and informal channels provide a rather distorted and unilateral image of the nature of childbirth, opportunities, and issues of competence, which do not facilitate real physical and psychological preparation for giving birth. This can influence the way and quality of birth-giving, the childbirth experience and, in the long run, the willingness to continue to have children.